Indeks Kesuburan Tanah Perkebunan Kopi Arabika (Coffea Arabica L.) di Agrowisata Pango-Pango Tana Toraja: Soil Fertility Index of Arabica Coffee Plantations (Coffea Arabica L.) in Pango-Pango Agrotourism, Tana Toraja - Tiara, Mutiara Cantika Garcia; Nathan, Muhammad; Jayadi, Muhammad (Universitas Hasanuddin, 2025)
Arabica coffee (Coffea arabica L.) plantations in Pango-Pango Agrotourism, Tana Toraja Regency, were surveyed for soil fertility index. Coffee plant production is greatly influenced by soil fertility, especially in the highlands, which are ideal habitats for Arabica coffee. This study aims to determine the soil fertility index of Arabica coffee plantations planted at different land heights in the community garden location of Pango-Pango Village, Tana-Toraja Regency at various elevations. The study was conducted using a survey method and laboratory analysis of nine soil samples from two elevation groups: 1500–1600 masl and 1600–1868 masl. The soil chemical parameters analyzed were pH, cation exchange capacity (CEC), organic C, total N, available P, K-dd, Ca-dd, Mg-dd, and Al-dd saturation. The results showed that the soil fertility index (SFI) varied from a rather low class to a rather high class, with soil pH generally acidic, and Al-dd relatively high. Although the temperature and micro humidity support the growth and production of coffee plants, due to the old age of the plants (around 28 years), low fertilizer input, and limited cultivation techniques, the productivity of the coffee plants is still relatively low. The soil fertility index at an altitude of 1500–1600 m above sea level is classified as rather low to moderate, with several soil chemical parameters that are not yet optimal. Meanwhile, at an elevation of 1600–1868 m above sea level, the soil fertility index increases to the moderate to rather high class even though the soil pH is still acidic and the Al-dd content is relatively high.